2020
DOI: 10.1111/nph.16890
|View full text |Cite
|
Sign up to set email alerts
|

Host selection shapes crop microbiome assembly and network complexity

Abstract: Plant microbiomes are essential to host health and productivity but the ecological processes that govern crop microbiome assembly are not fully known. Here we examined bacterial communities across 684 samples from soils (rhizosphere and bulk soil) and multiple compartment niches (rhizoplane, root endosphere, phylloplane, and leaf endosphere) in maize (Zea mays)-wheat (Triticum aestivum)/barley (Hordeum vulgare) rotation system under different fertilization practices at two contrasting sites. Our results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
355
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(446 citation statements)
references
References 91 publications
40
355
6
Order By: Relevance
“…The most dominant taxa as hub microbes belong to bacterial phyla Proteobacteria (21 OTUs), Actinobacteria (12 OTUs) and fugal phyla Ascomycota (20 OTUs). This is consistent with the finding that Proteobacteria, Actinobacteria and Ascomycota are the most abundant phyla in plants and soil (24,64).…”
Section: Hub Microbessupporting
confidence: 92%
See 1 more Smart Citation
“…The most dominant taxa as hub microbes belong to bacterial phyla Proteobacteria (21 OTUs), Actinobacteria (12 OTUs) and fugal phyla Ascomycota (20 OTUs). This is consistent with the finding that Proteobacteria, Actinobacteria and Ascomycota are the most abundant phyla in plants and soil (24,64).…”
Section: Hub Microbessupporting
confidence: 92%
“…It has been commonly recognized that the microbiota and their hosts form complex but well-orchestrated interaction networks (22,23). For example, the crop microbiome assembly is shaped by the host, even to a greater extent environmental factors (24).…”
Section: Introductionmentioning
confidence: 99%
“…Total DNA was extracted from the aforementioned samples using the FastDNA SPIN Kit for Soil (MP Biomedicals, Solon, USA) following manufacturer's instructions. The V5-V6 region of bacterial 16S rRNA gene (799F-1115R) [14,51], and the ITS2 region (fITS7-ITS4) of fungal ITS [16,52,53] were ampli ed ( Table S1). The primers sequence and PCR ampli cations were shown in Table S1.…”
Section: Dna Extraction and Ampli Cation Sequencingmentioning
confidence: 99%
“…Moreover, we also found that members of Sordariomycetes (18.27-46.34%) were distributed mainly in root tissues, while Tremellomycetes (1.21-30.59%) were distributed mainly in leaves and stems. This differentiation of the fungi in above-and belowground tissues could possibly be the result of resource utilization, which drives the rapid evolutionary radiation of microbes competing for resources, causing them to diverge and adapt to different niches to reduce competition [18,65].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the signi cant effects and selective pressure of host plants on endophytic fungal species and community composition [18][19][20][21][22]. For example, Yao et al [19] found that plant identity had a greater effect on endophytic fungal community composition than epiphytic fungi in the leaves of six mangrove species in South China, and Martínez-García et al [20] showed differences in the arbuscular mycorrhizal fungal communities under different shrubs in a semiarid environment.…”
Section: Introductionmentioning
confidence: 99%